Relational Encounters and Vital Materiality in the Practice of Craft Work - Bell, Emma; Vachhani, Sheena J. (Organization studies, 2020)
Practice-based studies of organization have drawn attention to the importance of the body as a site of knowledge and knowing. However, relational encounters between bodies and objects, and the affects they generate, are less well understood in organization studies. This article uses new materialist theory to explore the role of affect in embodied practices of craft making. It suggests that craft work relies on affective organizational relations and intensities that flow between bodies, objects and places of making. This perspective enables a more affective, materially inclusive understanding of organizational practice, as encounters between human and nonhuman entities and forces. We draw on empirical data from a qualitative study of four UK organizations that make bicycles, shoes and hand-decorated pottery. We track the embodied techniques that enable vital encounters with matter and the affective traces and spatial, aesthetic atmospheres that emerge from these encounters. We suggest that a concern with the vitality of objects is central to the meaning that is attributed to craft work practices and the ethical sensibilities that arise from these encounters. We conclude by proposing an affective ethics of mattering that constructs agency in ways that are not confined to humans and acknowledges the importance of orientations towards matter in generating possibilities for ethical generosity towards others.